Fe 전극 무한궤도형 전기분해장치를 이용한 하수 중 인과 질소제거 - 김민규(성수기공; 송영일; 이성기 (한국수처리학회지, 21(6), 2013)
It was developed an electrolysis device-type with a Fe electrode caterpillar. which was improved some troubles of a Fe electrode. The T-P removal rate was investigated according to various operation conditions. The pH change was not shown greatly at each processes. The nitrogen and phosphorus removal rate appeared higher an electrode plate with 920 mm than 600 mm depth. It was shown higher removal rate with three electrode plate than two. The 920 mm of an electrode printing interval was higher in nitrogen and phosphorus removal rates than 740 mm, but the difference was not large. Phosphorus effluent concentration according to an electric current change appeared lower 9 A, 14 A than 22 A. The electric current is higher, phosphorus removal rate is high because the response of iron ion is more active. The nitrogen removal rate was 50.1∼84.2% and a phosphorus removal rate was 96.0∼99.6% in combined sewage treatment processes with night soil and livestock wastewater. The nitrogen removal rate was 77.8∼89.7% and phosphorus removal rate was 77.7∼95.9% in sewage treatment processes. A phosphorus removal rate is higher in case of combined sewage treatment, which was good enough in the removal of nitrogen and phosphorus, Removal rate was shown as BOD 91.7∼98.6%, COD 90.0∼95.9%, SS 93.7∼98.8% in combined sewage treatment process with livestock and night soil. The iron production according to an electric current change was shown higher in case of 22 A than 9 A. The electric current is higher, The T-P removal rate is high. because of increasing the iron ion reactivity. KCI Citation Count: 3